Gender equality in the world, the European Union and Lithuania - Kublickienė, Lilija (Information & Media, 2018)
This article discusses the issue of gender equality as being an integral part of human rights and the fundamental basis of democracy. It is argued that the existence of legal guarantors is not a sufficient factor for the implementation of de facto gender equality. It is considered that the implementation of gender equality is a basic criterion of the quality of democrcy and reflects a certain change of values within a society. This article deals with the concepts of gender and gender equality, emphasizing their dynamism depending on the historical, political, cultural and social context, stressing that gender equality is still not implemented in many areas, although it is widely recognized that gender parity is important – not only in moral but also in social and economic terms. On the basis of report data from the Global Gender Gap, this article analyzes the indicators that disclose the differences of women and men statuses across four key areas: health, education, economy and politics. It investigates the current situation of gender equality on a global scale, the European Union and Lithuania, observing the changes that have taken place over the last decade (2006–2016). Keywords: human rights, gender, gender equality, gender gap, social integration, social exclusion